A novel tumor metastasis suppressor gene LASS2/TMSG1 interacts with vacuolar ATPase through its homeodomain. Issue 3 (22nd January 2013) - Yu, Wenjuan; Wang, Leiming; Wang, Yuewei; Xu, Xiaoyan; Zou, Pengcheng; Gong, Miaozi; Zheng, Jie; You, Jiangfeng; Wang, Hua; Mei, Fang; Pei, Fei
Abstract LASS2/TMSG1 was a novel tumor metastasis suppressor gene, which was first cloned by our laboratory from non‐metastatic and metastatic cancer cell variants of human prostate carcinoma PC‐3M using mRNA differential display in 1999. LASS2/TMSG1 could interact with the C subunit of vacuolar ATPase (V‐ATPase, ATP6V0C) and regulate V‐ATPase activity. In an attempt to provide molecular mechanism of the interaction between LASS2/TMSG1 and V‐ATPase, we constructed four variant transfectants containing different functional domain of LASS2/TMSG1 and stably transfected the variants to human prostate cancer cell line PC‐3M‐1E8 cell with high metastatic potential. Results showed that there were no obvious differences of V‐ATPase expression among different transfected cells and the control. However, V‐ATPase activity and intracellular pH was significantly higher in the variant transfectants with Homeodomain of LASS2/TMSG1 than that in the control using the pH‐dependent fluorescence probe BECEF/AM. Immunoprecipitation, immunofluorescence and immuno‐electron microscope alone or in combination demonstrated the direct interaction of Homeodomain of LASS2/TMSG1 and ATP6V0C. Loss of Homeodomain markedly enhanced the proliferation ability but weakened the apoptotic effect of LASS2/TMSG1 in PC‐3M‐1E8 cells. These lines of results for the first time contribute to the conclusion that LASS2/TMSG1 could regulate V‐ATPase activity and intracellular pH through the direct interaction of its Homeodomain and the C subunit of V‐ATPase. Their interaction could play important roles in the apoptosis of tumor cells. J. Cell. Biochem. 114: 570–583, 2013. © 2012 Wiley Periodicals, Inc.